2019
DOI: 10.15252/emmm.201809963
|View full text |Cite
|
Sign up to set email alerts
|

Dynorphin‐based “release on demand” gene therapy for drug‐resistant temporal lobe epilepsy

Abstract: Focal epilepsy represents one of the most common chronic CNS diseases. The high incidence of drug resistance, devastating comorbidities, and insufficient responsiveness to surgery pose unmet medical challenges. In the quest of novel, disease‐modifying treatment strategies of neuropeptides represent promising candidates. Here, we provide the “proof of concept” that gene therapy by adeno‐associated virus (AAV) vector transduction of preprodynorphin into the epileptogenic focus of well‐accepted mouse and rat mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…Gene therapy for epilepsy is a promising approach to treat the chronic phase of the pathology (Kullmann et al, 2014). Recent gene therapies target the symptoms (seizures) rather than the cause of epilepsy, for example, decreasing the excitability of excitatory neurons or potentiating inhibitory tone (Richichi et al, 2004;Noè et al, 2008;Wykes et al, 2012;Krook-Magnuson et al, 2013;Kätzel et al, 2014;Lieb et al, 2018;Agostinho et al, 2019;Wickham et al, 2019;Colasante et al, 2020). These therapies have been efficient in decreasing intrinsic neuronal excitability, synaptic transmission, and the number of seizures, in rescuing cognitive defects and also FIGURE 1 | Graphical representation of the potential role of homeostatic plasticity in the epileptic process.…”
Section: Therapeutic Interventions Based On the "Genetic Lead" Of Hommentioning
confidence: 99%
“…Gene therapy for epilepsy is a promising approach to treat the chronic phase of the pathology (Kullmann et al, 2014). Recent gene therapies target the symptoms (seizures) rather than the cause of epilepsy, for example, decreasing the excitability of excitatory neurons or potentiating inhibitory tone (Richichi et al, 2004;Noè et al, 2008;Wykes et al, 2012;Krook-Magnuson et al, 2013;Kätzel et al, 2014;Lieb et al, 2018;Agostinho et al, 2019;Wickham et al, 2019;Colasante et al, 2020). These therapies have been efficient in decreasing intrinsic neuronal excitability, synaptic transmission, and the number of seizures, in rescuing cognitive defects and also FIGURE 1 | Graphical representation of the potential role of homeostatic plasticity in the epileptic process.…”
Section: Therapeutic Interventions Based On the "Genetic Lead" Of Hommentioning
confidence: 99%
“… 4 In this work, Agostinho et al explored this prospect using the dynorphin system as a test case in preclinical models of TLE. 5 …”
Section: Commentarymentioning
confidence: 99%
“…Gene therapy for epilepsy has been performed as preclinical studies on rodent models chiefly targeting focal epilepsy such as temporal lobe epilepsy by local injection of viral vectors. Local induction of preprodynorphin, glutamate‐gated chrolide channel, neuropeptide Y and Y2, voltage‐gated potassium channel, and collybistin, etc., have demonstrated positive outcomes of vector‐mediated gene therapy for epilepsy 14–19 . We also have demonstrated that AAV8 vector‐mediated gene delivery of glutamic acid decarboxylase ( GAD ), a rate‐limiting enzyme for synthesizing inhibitory neuronal transmitter GABA, into the hippocampus of epileptic (EL) mice reduces seizure frequency and strength, but not seizure duration of tonic–clonic convulsion 18 .…”
Section: Introductionmentioning
confidence: 99%